Medical research charities and open access. Issue 4 (1st October 2013) - PINFIELD, Stephen
ABSTRACT: This paper provides an analysis of the attitudes and activities of UK medical research charities in relation to open access (OA). Both quantitative and qualitative data are presented derived from a recent survey of charities covering areas such as policy development, funding arrangements, and business process design for OA. Positions on key issues including green and gold OA, funding article‐processing charges (APCs), and publication licences are assessed. Modelling of potential APCs as a percentage of overall annual research spend is undertaken to show possible costs of a charged‐for gold system. Medical research charities clearly regard OA as important and some see it as an opportunity to further their mission. However, many expressed significant concerns particularly about the costs and expertise required to support OA. Further co‐ordination of policy development and action across the sector and with other stakeholders is recommended in order to help ensure optimal implementation of OA.